THE INFLUENCE OF LEADERSHIP STYLE ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN LHOKSEUMAWE POLICE - Ari Lasta Irawan; Marbawi; Adnan; Aiyub; Faisal Matriadi; Ikramuddin (CV. Radja Publika, 2023)
This study aims at the influence of digital leadership and transformational leadership on organizational commitment with job satisfaction as an intervening variable to the Lhokseumawe police station. For the dependent variable of this study is digital leadership and transformational leadership, the independent variable is the organizational commitment of the police station. Intervening variables are job satisfaction. The population in this study was the Police Personal of the Lhokseumawe District Police which numbered 575, the sampling technique used proportionate stratified random sampling and obtained a sample of 170 respondents who were police officers of the Lhokseumawe police station, the research method used is a quantitative method for data analysis method using Structural Equation Modeling (SEM). The results of this study indicate that, digital leadership has a significant effect on job satisfaction, transformational leadership has a significant effect on job satisfaction, leadership has an effect on organizational commitment, transformational leadership has a significant effect on organizational commitment, job satisfaction has a significant effect on organizational commitment,.